2001
DOI: 10.1007/s11746-001-0260-9
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of menhaden oil and partially hydrogenated menhaden oil: Characterization of triacylglycerol fractions

Abstract: Menhaden oil (MO) and partially hydrogenated menhaden oil (PHMO) were dry-fractionated and solvent-fractionated from acetone. After conversion to fatty acid methyl esters, the compositional distribution of saturated, monounsaturated, trans, and n-3 polyunsaturated fatty acids (PUFA) in the isolated fractions was determined by gas chromatography. Acetone fractionation of MO at −38°C significantly increased the n-3 PUFA content in the liquid fractions over that of starting MO (P < 0.05). For PHMO, liquid fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…When comparing the solid fractions with their respective liquid fractions, it was found that the SFC values of all solid fractions were higher than the liquid fractions at all temperatures of measurement. The SFC increase and decrease in the solid and liquid fractions, respectively, from the original fat is what to be expected after fractional crystallization as reported previously 6,10,21 . This is because the solid fraction usually contains higher content of high-melting TAGs than the native fat and the liquid fraction.…”
Section: Solid Fat Contentsupporting
confidence: 89%
“…When comparing the solid fractions with their respective liquid fractions, it was found that the SFC values of all solid fractions were higher than the liquid fractions at all temperatures of measurement. The SFC increase and decrease in the solid and liquid fractions, respectively, from the original fat is what to be expected after fractional crystallization as reported previously 6,10,21 . This is because the solid fraction usually contains higher content of high-melting TAGs than the native fat and the liquid fraction.…”
Section: Solid Fat Contentsupporting
confidence: 89%
“…So that formation of glyceride crystal would be faster. Solvent (typically acetone) crystallization is used for promoting TAG crystal formation, because TAG at low temperature generally form more stable crystals with solvent than without solvent (Lee et al, 2001). Talbot et al, (2006) reported that an increase in the concentration of solution would be lead to the formation of bigger crystal.…”
Section: The Effects Of Cfame-to-acetone Ratio On Yieldmentioning
confidence: 99%
“…The esters are subsequently fractionated by various methods to obtain higher concentrates of EPA and DHA (Shahidi and Wanasundara 1998) by means of vacuum or short path distillation (Ackman et al 1973;Breivik et al 1997), solvent crystallization (Lee 2003), or urea complexation (Senanayake and Shahidi 2000;Gámez-Meza et al 2003;Zuta et al 2003). These conventional methods often require the use of flammable and toxic organic solvents or elevated process temperatures, which can lead to polymerization and degradation of thermally labile PUFA (Staby and Mollerup 1993;Lee and Foglia 2001). Selective enzymatic hydrolysis of fish oil TGs using fatty acid-specific lipases can be used as well for the separation and concentration of EPA and DHA from other fatty acids present in fish oils (Linder et al 2002;Ramírez Fajardo et al 2006).…”
Section: Lipid-based Nutraceuticalsmentioning
confidence: 99%